Endovascular treatment evolution for pure intraorbital arteriovenous fistula: Three case reports and literature review. Issue 2 (April 2017) - Lv, Xianli; Li, Wei; Liu, Aihua; Lv, Ming; Jiang, Chuhan
Background and importance: Intraorbital arteriovenous fistulas (IOAVFs) are rare and cause eye redness, exophthalmos, blurry vision and bruit. Whereas in the past they were treated conservatively, surgically or transarterially, recent developments in transvenous embolization have improved their treatment. In this paper the authors report three cases of IOAVFs treated endovascularly and review the evolution of treatment options. Methods: Three cases of purely IOAVF enrolled in our center were reported and a PubMed literature search was performed using "pure intraorbital arteriovenous fistula" and "arteriovenous fistula of the optic nerve sheath." A total of 21 papers were reviewed in full, focusing primarily on the treatment and outcomes. Results: A total of 26 patients were obtained, including our three patients and 23 patients reported in the literature. In nine patients treated conservatively, four spontaneous occlusions, one visual deterioration and four cases with unknown outcome were reported. In another 18 patients, 29 therapies (including five surgical treatment, 11 transarterial embolizations and 13 transvenous embolizations) were attempted and resulted in 12 cures, five visual deteriorations and one without reported outcome. More recently, transvenous embolization has become the mainstay of IOAVF treatment. Of the 21 patients assessed between 2000 and 2013, a transvenous approach was attempted in 13 patients; nine patients were cured without any adverse events. Conclusion: Development and improvement of transvenous techniques are found to be safe and effective for patients with IOAVF.